2013
DOI: 10.1103/physrevlett.111.153601
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Impedance-MatchedΛSystem by Dressed-State Engineering

Abstract: In one-dimensional optical setups, light-matter interaction is drastically enhanced by the interference between the incident and scattered fields. Particularly, in the impedance-matched Λ-type three-level systems, a single photon deterministically induces the Raman transition and switches the electronic state of the system. Here we show that such a Λ system can be implemented by using dressed states of a driven superconducting qubit and a resonator. The input microwave photons are perfectly absorbed and are do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 33 publications
1
66
0
Order By: Relevance
“…This can be observed in microwave spectroscopy as perfect absorption of the incident field and frequency down-conversion of the reflected field [10]. A schematic of the measurement setup at the 10 mK stage of a dilution refrigerator is shown in Fig.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This can be observed in microwave spectroscopy as perfect absorption of the incident field and frequency down-conversion of the reflected field [10]. A schematic of the measurement setup at the 10 mK stage of a dilution refrigerator is shown in Fig.…”
mentioning
confidence: 99%
“…Moreover, an artificial atom coupled directly with a microwave transmission line demonstrates near-perfect reflection of the incident field [8,9]. Recently, we have theoretically shown that an impedance-matched Λ system can be implemented by using the dressed states of a driven circuit-QED system [10]. Although Λ and Δ systems have been proposed theoretically [11][12][13][14] and implemented experimentally with a flux qubit by using the lowest three levels of its asymmetric double-well potential [15][16][17], realizing an impedance-matched Λ system has remained elusive.…”
mentioning
confidence: 99%
See 3 more Smart Citations